2021
DOI: 10.2217/fon-2020-1065
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of prognostic nomograms in patients with hepatocellular carcinoma: a population-based study

Abstract: Background: Hepatocellular carcinoma (HCC) is one of the most common malignant tumors. The existing staging system has a limited budget capacity for HCC recurrence. The authors aimed to establish and verify two nomogram models to predict disease-free survival (DFS) and overall survival (OS) in patients with HCC. Methods: Patients diagnosed with HCC between August 2011 and March 2016 were recruited. Data were randomly divided into a training cohort and a validation cohort. Based on univariate and multivariate C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…AST and ALP have been recognized as independent risk factors for the early recurrence of cHCC-CC. Previous studies on early recurrence of HCC also highlight the independent influence of AST [27,28] and ALP [29,30] as contributing factors. Similarly, MVI has been established as a strong and independent predictor of early postoperative recurrence of cHCC-CC [12,13,15,22], likely because it is associated with the cytokines and proteins secreted by stromal cells in the tumor microenvironment that promote angiogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…AST and ALP have been recognized as independent risk factors for the early recurrence of cHCC-CC. Previous studies on early recurrence of HCC also highlight the independent influence of AST [27,28] and ALP [29,30] as contributing factors. Similarly, MVI has been established as a strong and independent predictor of early postoperative recurrence of cHCC-CC [12,13,15,22], likely because it is associated with the cytokines and proteins secreted by stromal cells in the tumor microenvironment that promote angiogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Currently, studies have shown that tumor size, tumor number, pathological grading, staging classification, microvascular invasion (MVI), and various biomarkers correlate with patient prognostic outcomes (7)(8)(9)(10). However, this traditional prognostic model, due to its invasive examination, existing comorbidities, and geographical differences in staging classification make its clinical application limited, with the decreased granularity in predicting outcomes, lower accuracy, specificity, and sensitivity, and cannot obtain information on tumor heterogeneity and provide patients with accurate prognostic information to the extent that it affects the clinical decisionmaking treatment process of patients, resulting in poor prognosis and reduced OS (8,(11)(12)(13). In addition, Traditional imaging features, although capable of observing diseaserelated progression, are poorly effective in predicting prognosis.…”
Section: Introductionmentioning
confidence: 99%